Deconstructing Matrilineal Parenting: A Role-Specific Analysis of Authoritative, Authoritarian, and Permissive Practices - MHD Natsir; Melvina Melvina; Ahmad Jazimin Jusoh; Marina Lidya (Journal of Nonformal Education, 2026)
Background: While matrilineal parenting influences adolescent character, Western-derived parenting typologies are often applied monolithically, obscuring nuanced, role-specific practices within kinship-based systems. Aim: This study examines how parenting practices by mothers, fathers, and maternal uncles (mamak) are differentially associated with twelve adolescent character strengths in Minangkabau, Indonesia. Methods: A cross-sectional survey of 296 primary caregivers used a culturally contextualized questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test multivariate relationships between nine parenting dimensions (three practices × three caregivers) and character outcomes. Results: Mother’s authoritative practices positively predicted all character strengths. Mamak’s authoritarian practices displayed dual effects: positively predicting discipline and respect but negatively predicting honesty and creativity. Father’s authoritative practices fostered independence and confidence, while his permissiveness was particularly detrimental. Discussion/Implication: Findings reveal a specialized “parenting ensemble,” where effects depend on the cultural legitimacy of the caregiver’s role. This challenges universal parenting models and suggests family support programs must be role-specific: strengthening authoritative communication universally, refining the mamak’s disciplinary approach, and clarifying the father’s unique supportive niche to holistically foster adolescent character